Results of a Quality Assurance Program for Detection of Cytomegalovirus Infection in the Pediatric Pulmonary and Cardiovascular Complications of Vertically Transmitted Human Immunodeficiency Virus Infection Study - Demmler, Gail J. (American Society for Microbiology, 2000)
A quality assurance program was established by the Pediatric Pulmonary and Cardiovascular Complications of Vertically Transmitted Human Immunodeficiency Virus Type 1 Infection Study Group for monitoring cytomegalovirus (CMV) antibody and culture results obtained from nine different participating laboratories. Over a 3-year period, every 6 months, each laboratory was sent by the designated reference laboratory six coded samples: three urine samples for CMV detection and three serum samples for CMV immunoglobulin G (IgG) and IgM antibody determination. Overall, the participating laboratories exhibited the following composite performance statistics, relative to the reference laboratory (sensitivity and specificity, respectively): 100 and 97.4% for CMV cultures, 95.5 and 94.4% for CMV IgG antibody assays, and 92.6 and 90.2% for CMV IgM assays. The practice of having individual laboratories use different commercial methods and reagents for CMV detection and antibody determination was successfully monitored and provided useful information on the comparable performance of different assays.